Better policies for sustainable development 2016 : a new framework for policy coherence - Organisation for Economic Co-operation and Development (OECD, 2016)
Summary.
Keywords: kestävä kehitys; ympäristönsuojelu; kansainvälinen ympäristönsuojelu; elintarviketurvallisuus; talouskasvu; talouspolitiikka